Power and the traditional culture of a region in the dynamics of magazine representations: Tuva on the pages of the Sibirskie Ogni magazine (1920s — 2010s) - Krasilnikova, Ekaterina I.; Valdman, Igor A. (The New Research of Tuva, 2020)
The article examines the representations of the past and traditional culture of the Tuvan people on the pages of the “Sibirskie Ogni” (“Siberian Lights”), the oldest in Siberia (and one of the oldest surviving in Russia) literary, art and socio-political magazine. Founded in the 1920s, Sibirskie Ogni will be studied here in the context of developing a state policy of memory.Given that during the 20th century Tuva underwent enormous modernization, the authors explain why collective memory of the past is important for traditional society in terms of maintaining socio-political order. Also shown is how the Soviet periodical helped the state authorities politicize Tuvan history.The authors have examined over 30 publications on history, culture and literature of Tuva which appeared in the magazine, as well as editorial correspondence and documentation. The succession of these sources shows the transformation of how the magazine’s authors represented traditional Tuvan culture. From harsh criticism and aversion the tone of these publications slowly changed to reveal an attempt to see it as a rediscovered source of the region’s unique development model.The article traces four stages of constructing the representations of history and traditional Tuvan culture in the Sibirskie Ogni: mid-1920s to late 1940s, late 1940s to early 1980s, the rest of the 1980s and the early 1990s to present times.
Keywords: politics of memory; social memory; traditional culture; ideology; Tuva; Tuvans; Tuvan culture; Sibirskie Ogni